Death of distance? Economic implications of infrastructure improvement in Russia - David Brown; Marianne Fay; Somik V. Lall; Hyoung Gun Wang; John Felkner (EIB Papers, 2008)
We examine the economic implications of infrastructure investment policies that try to improve economic conditions in Russia's peripheral regions. Our analysis of firm-level industrial data for 1989 and 2004 highlights a 'death of distance' in industrial location, with increasing concentration of new firms in regions with good market access. We assess the geographic determinants of growth econometrically and identify market size and proximity to Moscow and regional infrastructure as important drivers of productivity for new and for privately-owned firms. Simulations show that the benefits of infrastructure improvements are highest in the country's capital region where economic activity is already concentrated. Policies that divert public investment towards peripheral regions run the risk of slowing down national economic growth.
Keywords: 330; Verkehrsinvestition; Peripheres Gebiet; Regionale Konzentration; Räumliche Verteilung; Wirtschaftswachstum; Russland